2004
DOI: 10.1021/ma040010a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Azobenzene-Containing Polymer Membranes That Function in Photoregulated Molecular Recognition

Abstract: Selective, stable, molecularly imprinted polymers having intrinsic photoresponsive properties were synthesized for the purpose of photoregulated binding of a predetermined ligand. Highly crosslinked, free-standing polymer membranes were synthesized from an optimized mixture of two crosslinkerssethylene glycol dimethacrylate and tetraethylene glycol diacrylate. For synthesizing molecularly imprinted polymers, p-phenylazoacrylanilide (PhAAAn) was used as a new photoresponsive functional monomer. A study of the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…[14,17] Rate constants for the trans → cis and cis → trans isomerization of MPABA were found to be 7.59 × 10 -4 and 14.68 × 10 -4 s -1 , respectively, which is quite comparable with other literature values. [18] …”
Section: Synthesis and Photoisomerization Properties Of The Functionasupporting
confidence: 88%
See 1 more Smart Citation
“…[14,17] Rate constants for the trans → cis and cis → trans isomerization of MPABA were found to be 7.59 × 10 -4 and 14.68 × 10 -4 s -1 , respectively, which is quite comparable with other literature values. [18] …”
Section: Synthesis and Photoisomerization Properties Of The Functionasupporting
confidence: 88%
“…Minoura et al reported the use of p-phenylazoacrylanilide as a functional monomer for the fabrication of MIP membranes that showed photocontrollable affinity for dansylamide. [14] Marx-Tibbon and Willner, on the other hand, reported the use of another photoresponsive system for molecular-imprinting purposes. They used an acrylatederivatized merocyanine monomer for the imprinting of tryptophan in a molecularly imprinted membrane, which exhibited photocontrollable selective transport properties towards the imprinted amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…Since photo-isomerization of a chromophore had a great influence on the binding site, the resulted MIP membranes exhibited a reversible absorption/release of the template dansylamide (DA), and a better selectivity towards its analogue, dansyl-L-leucine (DL) and N,N-dimethylnaphthylamine (DMN). However, the binding capacity and the selectivity of the MIP membranes were not high, which may be attributed to the weaker interactions between the azobenzene functional monomers and target molecules [82].…”
Section: Photo-responsive Molecularly Imprinted Polymersmentioning
confidence: 93%
“…Photoinduced catalysis is also possible, for instance, using molecules where only the cis form is catalytically active (Wuerthner and Rebek, 1995). Extension of the molecular imprinting technique to azo polymers allows for photoswitching of binding activity with respect to the imprinted molecule (Minoura et al, 2004). …”
Section: Macroscopic Motionmentioning
confidence: 99%